2006
DOI: 10.3758/bf03193432
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of faces and complex objects in younger and older adults

Abstract: We examined whether (1) age-associated impairments in face recognition are specific to faces or also apply to within-category recognition of other objects and (2) age-related face recognition deficits are related to impairments in encoding second-order relations and holistic information. In Experiments 1 and 2, we found reliable age differences for recognition of faces, but not of objects. Moreover, older adults (OAs) and younger adults (YAs) displayed similar face inversion effects. In Experiment 3, unlike YA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(131 citation statements)
references
References 62 publications
11
118
2
Order By: Relevance
“…Previous studies examined either more basic processes of face perception (Boutet & Faubert, 2006;Komes et al, 2014bKomes et al, , 2015Konar et al, 2013;Meinhardt-Injac, Persike, & Meinhardt, 2014a;Wiese et al, 2013) or name generation (James, 2004(James, , 2006James, Fogler, & Tauber, 2008) in older adults, two processes that are often assumed as reflecting opposite end points in the sequence of processing steps in person recognition (Bruce & Young, 1986Hanley, 2011). The present study examined the steps in-between these end points.…”
Section: Cognitive Ageing In Face and Person Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies examined either more basic processes of face perception (Boutet & Faubert, 2006;Komes et al, 2014bKomes et al, , 2015Konar et al, 2013;Meinhardt-Injac, Persike, & Meinhardt, 2014a;Wiese et al, 2013) or name generation (James, 2004(James, , 2006James, Fogler, & Tauber, 2008) in older adults, two processes that are often assumed as reflecting opposite end points in the sequence of processing steps in person recognition (Bruce & Young, 1986Hanley, 2011). The present study examined the steps in-between these end points.…”
Section: Cognitive Ageing In Face and Person Recognitionmentioning
confidence: 99%
“…It is known that recognition memory for faces decreases with higher age (e.g., Bartlett & Leslie, 1986;Hildebrandt, Sommer, Herzmann, & Wilhelm, 2010;Wiese, Schweinberger, & Hansen, 2008;Wolff, Wiese, & Schweinberger, 2012), whereas more basic abilities of face perception (such as "holistic" or "configural" processing of faces) appear to remain largely intact (Boutet & Faubert, 2006;Konar et al, 2013;Meinhardt-Injac et al, 2014b; but see Wiese, Kachel, & Schweinberger, 2013). Using structural equation modelling to examine individual differences in face processing, Hildebrandt and colleagues (2010) reported decreases in face memory to start in the fifth decade and decreases in face perception to start in the seventh decade of life.…”
Section: Effects Of Cognitive Ageing In Face and Person Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous descriptions of age-related declines in visual memory have shown deficits with faces but not other figures, 29 or environmental scenes. 30 Our finding of figural and scene memory impairments in normal aging may reflect the more naturalistic demands of a navigational environment.…”
Section: Figure 4 Mean Scores On Each Subtest From the Real-world (A)mentioning
confidence: 99%
“…The reduction in face processing proficiency, however, may not be solely a function of memory or learning changes, as older observers perform more poorly than their younger counterparts even when the need for memory or learning of faces is minimized (Boutet & Faubert, 2006). The age-related decline is also apparent when the task is purely perceptual and is based solely on shape and facial geometry; for example, in one recent study, faces shown from the same vantage point were equally well discriminated by observers, independent of age, but faces shown from different viewpoints were more poorly discriminated by older observers and there was no improvement in performance even with prolonged exposure duration (Habak, Wilkinson, & Wilson, in press).…”
Section: Introductionmentioning
confidence: 99%